2009
DOI: 10.1002/hyp.7283
|View full text |Cite
|
Sign up to set email alerts
|

Sediment storage in the shallow hyporheic of lowland vegetated river reaches

Abstract: Abstract:Excessive fine sediment deposition on the river channel bed together with colmation of finer sediments within the hyporheic are now linked to the degradation of the aquatic habitats of gravel bed rivers in permeable catchments. Previous studies of chalk rivers (associated with outcrops of calcareous rock) have demonstrated the important role of aquatic vegetation in trapping fine sediment on the river channel bed. This research investigated the spatio-temporal patterns and composition of fine sediment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 52 publications
1
44
2
Order By: Relevance
“…Heppell et al 2009), although the median particle size (D 50 = 164 μm) is greater than other studies (e.g. Marttila and Kløve 2014;7-60 μm).…”
Section: In-channel Sediment Storagecontrasting
confidence: 55%
See 2 more Smart Citations
“…Heppell et al 2009), although the median particle size (D 50 = 164 μm) is greater than other studies (e.g. Marttila and Kløve 2014;7-60 μm).…”
Section: In-channel Sediment Storagecontrasting
confidence: 55%
“…Walling et al 2003;Collins and Walling 2007a, b). Others have observed mixed patterns, arguing for the importance of cycles of vegetation growth and senescence (Heppell et al 2009) or the greater influence of flow conditions and local channel characteristics (Marttila and Kløve 2014). The latter authors also found that, in a catchment exploited for peat and wood in central Finland, the high volumes of sediment delivered by headwater tributaries were quickly conveyed downstream; similar dynamics have been reported in Mediterranean streams (Francke et al 2014;Piqué et al 2014).…”
Section: In-channel Sediment Storagementioning
confidence: 68%
See 1 more Smart Citation
“…A variety of herbs, shrubs and trees grow in stream channels, increasing bed roughness and driving specific relationships with hydraulic conditions and the development of preferential flow pathways (Corenblit et al, 5 2007). Vegetation also alters stage-discharge relationships that affect hyporheic flow (Champion and Tanner, 2000;Harvey et al, 2003;Heppell et al 2009). Jones et al (2008) demonstrated that in-channel vegetation restructures hyporheic flow patterns by creating temporally dynamic deviations of hydraulic gradients.…”
Section: Ecological Factors: In-channel Vegetationmentioning
confidence: 99%
“…Recent flume-based and field studies (e.g. Wharton et al 2006;Heppell et al 2009;Harvey et al 2011;Jones et al 2011;Salant 2011) have also demonstrated that both macrophytes and periphyton are important in controlling sediment deposition and resuspension within river channels. According to Harvey et al (2011) "physical-biological interactions and resulting effects on sediment and nutrient redistribution are arguably some of the principal drivers of ecological function and hydrogeomorphic evolution of aquatic systems….. and deserve more study".…”
Section: In-channel Sediment-vegetation Dynamicsmentioning
confidence: 99%